Rehumanizing Education: Teaching and Learning as Co-Constructed Reflexive Praxis (LEARNing Landscapes, 2021)
Teaching and learning are profoundly personal experiences, yet systems of education often prioritize ubiquitous agendas that alienate rather than engage. Creating space for individuals and their lived experiences has the capacity to transform the classroom from a place of containment to one of expansiveness. Resisting the tendency of education to think dichotomously about teaching/learning, theory/practice, and self/other, we engage here as two learners who happen to have shared a graduate program, one as teacher and one as student. Influenced by post-qualitative inquiry (St. Pierre, 2017a; St. Pierre, 2017b) and post academic writing (Badley, 2019), we engage reflexively to consider the experience of this shared learning journey.
Keywords: post-qualitative inquiry; post-academic writing; reflexive inquiry; poetic inquiry; praxis